Study of clinical and epidemiological risk factors in the development of precancerous cervical diseases - Zokhidova Begoyim (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Cervical intraepithelial neoplasia (CIN) occupies a decisive position within the oncological continuum, representing the interval during which targeted clinical intervention yields the greatest preventive dividend. This prospective cohort study enrolled 312 women aged 22–57 years attending colposcopy referral services at two gynecological oncology centers over an 18-month period. Exposure variables encompassed HPV genotypic profiles, duration of viral carriage, parity, contraceptive history, tobacco use, and healthcare utilization frequency. Histopathologically confirmed biopsy results served as the primary outcome measure. Binary logistic regression with stepwise covariate selection identified independent predictors of high-grade dysplasia. Persistent infection with HPV genotypes 16 or 18 exceeding 18 months constituted the dominant risk determinant (adjusted OR = 5.3; 95% CI: 3.2–8.7; p < 0.001). Current smoking was independently associated with CIN II–III progression (OR = 2.1; 95% CI: 1.3–3.4; p = 0.002). Irregular screening intervals exceeding 30 months and multiparity of three or more deliveries further compounded lesion severity. A combined predictive index derived from four independent variables attained an AUC of 0.84, demonstrating satisfactory discriminative performance. The results advocate for HPV persistence–based triage protocols integrated with behavioral risk profiling as the operational standard for regional cervical cancer prevention programs.